A Forensic Linguistics Study of Provocative Speech Acts by Politicians on Social Media Platforms - Wiwien Pratiwi Harsa; Arifulhak Arifulhak (English Teaching and Linguistics Journal (ETLiJ), 2022)
The goals of this study are to describe the sorts of provocative speech acts perpetrated by politicians on YouTube social media, and to explain the forms of provocative speech acts perpetrated by politicians on YouTube social media. The data in this study comes from YouTube social media languages that are expected to feature provocative criminal behaviors. The social media platform YouTube served as the studys data source. The descriptive qualitative method was used in this study, as well as data gathering strategies such as watching and documentation. The procedures of identifying, classifying, and analyzing were used to analyze the data. The findings show that politicians social media utterances comprise literal indirect speech acts, but locutionary speech acts use declarative, imperative, interrogative locutions, expressive illocutions, and induce the listener to consider perlocutions (make the listeners think about it). These statements are in violation of Articles 160 and 161 of the Criminal Code, which deal with sedition. Keywords: Forensic Linguistics, Provocative Speech Acts, Politicians, and Social Media.